Investigation of hydrogen bonding in aqueous acetone mixtures by Raman spectroscopy. (5th June 2021) - Yang, Bo; Liu, Zhe; Wang, Shenghan; Sun, Chenglin; Men, Zhiwei
Abstract: The Raman spectra of aqueous acetone solution with various concentrations were measured at room temperature and atmospheric pressure. We find that the peak at 3400 cm −1 showed a significant blue shift at V a ( V a represents the volume fraction of acetone) >0.2, whereas the peak at 197 cm −1 exhibited red shift under the same conditions. The results indicate that the cage structure of water is destroyed and a large number of water molecules form acetone–water complex with acetone molecules. Moreover, the acetone–water complex from the acetone–(water)2 structure gradually changed to acetone–water at V a > 0.6. In addition, the Raman spectra of methyl groups were also studied, which illustrates that the methyl group of acetone forms a hydrophobic hydrated structure. Finally, the phase transition process of acetone–water complex in methanol–water binary solution was discussed. Abstract : We discussed the intermolecular hydrogen bonding and the corresponding molecular associations in the acetone–water binary solution by the concentration‐dependent Raman spectroscopy. The results illustrated that the cage structure of water was destroyed at V a > 0.2. Moreover, the acetone–water complex from the acetone–(water)2 structure gradually changed to the acetone–water at V a > 0.6. Raman spectra of methyl group indicated that the methyl group of acetone formed a hydrophobic hydrated structure.